Loretta Little looks back : three voices go tell it - Pinkney, Andrea Davis (Little, Brown and Company, 2022)
Loretta, Roly, and Aggie B. Little relate their Mississippi family's struggles and triumphs from 1927 to 1968 while struggling as sharecroppers, living under Jim Crow, and fighting for Civil Rights.